A novel technique fast optimizing the layout parameters of planar spiral inductor - Wang Tao; Wang Yong; Cao Ming; Chen Kangsheng (ASIC, 2003. Proceedings. 5th International Conference on, 2003)
Based on the physical model of planar spiral inductor and the closed-form inductance expression proposed by Jenei etc., this paper develops a novel technique fast optimizing the layout parameters of spiral inductor. It has been shown Jenei's formula is more accurate than the closed-form formulas presented before, and this paper further demonstrates that Jenei's formula can yield a speed about two magnitude order faster than GreenHouse method with a comparable accuracy. Mathematical analysis of Jenei's formula immediately leads to the derivation of BSA to search out all layout parameters satisfying constraints quickly, then the set with the highest Q can be identified. Experiments show that BSA's searching speed is about three magnitude order faster than the incremental searching algorithm based on GreenHouse method, while the accuracy of both algorithms are similar. The efficiency and accuracy of the optimizing technique are demonstrated by experiments.